A review of motion estimation methods for non-invasive ultrasound motion and emerging strain imaging methods of carotid artery plaques. (9th May 2011) - Murillo, Sergio; Pattichis, Marios S.; Barriga, E. Simon
Non-invasive ultrasound imaging of carotid plaques is used in routine clinical evaluation of atherosclerosis and stroke. Strain imaging of the atherosclerotic plaques represents a very promising, emerging application of ultrasound imaging because it can assess plaque vulnerability without the risks of intervention. The promise of strain imaging includes the development of advanced diagnostic tools that can be used to predict plaque rupture. This review paper presents the fundamental assumptions and methods that can be used to extract motion estimates from ultrasound images. In terms of assumptions, both the constant and non-constant brightness models are presented. The most commonly used energy functionals are presented, along with both local and global solutions. Motion and strain imaging examples are also provided to demonstrate the methods. Our goal is that this review will facilitate the development of new, reliable strain imaging methods that can be used to assess the risk of plaque rupture.